The Influence of Price and Product Quality on Customer Satisfaction at the Cressida Fashion Brand in Palembang - Santoso, Renaldi Ari; Widagdo, Herry (Sean Institute, 2025)
The purpose of this study is to analyze the effect of price, product quality, service quality and emotional on customer satisfaction at the Cressida fashion brand in Palembang partially and this study analyzes the effect of price, product quality, service quality and emotional on customer satisfaction at the Cressida fashion brand in Palembang simultaneously. The method used for data collection is by distributing questionnaires to 398 respondents. The type of research used is a descriptive quantitative method. The sampling technique uses nonprobability sampling with the purposive sampling method and uses the help of the SPSS version 26 application. The results of this study indicate that the partial test (t-test) of the price, product quality, service quality and emotional variables have a positive and significant effect on customer satisfaction. The simultaneous test (F-test) proves that the independent variables are price, product quality, service quality and emotional have a positive and significant effect on the dependent variable, namely customer satisfaction.